A Rare Mucoepidermoid Carcinoma of the Lacrimal Gland - Zhen, Wendy; Khattar, Alanna (Canadian Journal of Optometry, 2023)
Purpose This case report demonstrates the importance of ruling out orbital masses as an etiology in cases of non-resolving proptosis, upper eyelid edema, and diplopia. This report also reviews the key testing required to properly identify or rule out orbital masses. Case Report A 40-year-old African American male presented for persistent right upper eyelid edema, proptosis, and diplopia in up-gaze following a physical assault more than one year ago. Extraocular muscle testing revealed moderate restriction in up-gaze and mild restriction in abduction of the right eye. Anterior segment examination was remarkable for moderate right upper eyelid chemosis and proptosis. Magnetic resonance imaging (MRI) of the orbits revealed a mass originating from the right lacrimal gland with marked proptosis of the right globe. Biopsy results of the right lacrimal gland mass diagnosed the patient with a rare intermediate to high grade mucoepidermoid carcinoma of the right lacrimal gland. Management included surgical removal of the lacrimal gland tumor, treatment of keratoconjunctivitis sicca following excision of lacrimal gland tissue, and long-term co-management between oculoplastics and oncology. Conclusion Proptosis, upper eyelid edema, and/or diplopia can be expected after a recent ocular trauma, but there can also be more serious etiologies with similar presentations. This case report highlights the importance of further investigation and neuro-imaging when a patient presents with these types of non-resolving clinical signs.